ASSESSMENT OF SELF-CARE IN HEART FAILURE PATIENTS - Juliana Medeiros; Carolina de Araújo Medeiros (Universidade Federal do Paraná, 2017)
The objective in this study was to characterize the clinical and sociodemographic profile of heart failure patients and to describe the self-care behavior. Descriptive and cross-sectional study with a non-probabilistic sample of 57 cardiology nursing patients at a public hospital in Recife, Brazil, between May and September 2016. The self-care was assessed by means of the Self-Care of Heart Failure Index version 6.2, Brazilian version. The participants' mean age was 62.9 years; 31 (54.4%) men; 36 (63.2%) literate; 26 (45.6%) suffering from hypertensive etiology and 30 (52.6%) in functional class III. The mean scores for the subscales indicated inappropriate self-care (self-care maintenance: 43.3; self-care management: 37.5 and confidence in self-care: 54.3). Higher scores were associated with education, with literate participants obtaining a mean score of 61 points (p=0.002). Investments are needed to improve self-care and nursing can play a relevant role in this improvement.